Improvement in Sperm Quality of Mice Due to Mono Sodium Glutamate (MSG) Exposure with Zingiber officianale var Rubrum Extract - Putri, Arista Adityasari (Jurnal Biologi Tropis, 2025)
Technological advances have made many things easier in various fields, one of which is the processing of sugar cane, which is used as a food flavoring and contains monosodium glutamate. These disorders can be reduced by administering Red Ginger as one of the antioxidant compounds that can enhance and improve sperm motility. The purpose of this study was to prove the increase in sperm motility in male rats exposed to MSG with the administration of red ginger. This study used a randomized post-test only control group experimental design, with 30 Wistar rats aged 13-14 weeks and weighing 200-300 grams.  Statistical analysis was performed using One-Way ANOVA and Chi-Square tests. The results of this study show that in the sperm motility examination, there were 7 rats with motile sperm in the control group and group 1 (MSG), while in group 2 (MSG and Red Ginger) there were 8 rats with motile sperm. The group subjected to MSG plus red ginger therapy had the highest median sperm motility value among the three groups in this study, according to a comparison of their median values. The treatment of red ginger extract to male rats exposed to MSG tends to improve sperm motility, it can be concluded. Further research recommendations could include adding more varied treatment times so that more significant differences can be seen with graduated therapeutic doses.